The status of Donkeys (Equus asinus) in Greece - ARSENOS (Γ. ΑΡΣΕΝΟΣ), G.; GELASAKIS (Α. Ι. ΓΕΛΑΣΑΚΗΣ), A. I.; PAPADOPOULOS (ΕΛ. ΠΑΠΑΔΟΠΟΥΛΟΣ), E. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
The paper presents, for the first time, information about donkeys (Equus asinus) in Greece. Most of the information was obtained from interviews of donkey owners, using a purpose built questionnaire. The population of donkeys in Greece showeda remarkable decrease over the last decades. From 508,000 in 1955, there were only 14,570 in 2008, a decrease of 97%. The existing donkeys were characterised by a large diversity in phenotypes. The lack of any breeding programme for donkeys, the importation of jacks from foreign breeds, the loss of interest and under-appreciation, together with the ignorance of health and welfare needs of such animals were the main reasons that shaped the current status. The health and welfare status of donkeys differed enormously across different areas of Greece, reflecting differences in the cultural, economical and "emotional" importance of individual animals. It was revealed that many problems were associated with diseases originating in malnutrition, parasites and bad husbandry management. Moreover, current and future trends, resulting from social and economical developments in rural areas of Greece, are discussed. Given the trends currently affecting the status of donkeys in Greece we concluded that a conservation policy should be adopted, because the number of donkeys will continue to fall.